The Size of Residual Patella Tendon Defect Following Bone-Patella Tendon-Bone Autograft Harvest Does Not Affect Patient-Reported Outcome Measures - Pilc, Emily M.; Stephens, Senah E.; Liu, Rebecca P.; Meyers, Jillian L.; Worcester, Katherine S.; Patton, Robert B.; Griffin, Justin W.; Bonner, Kevin F. (The Journal of Knee Surgery, 2025)
Consequences of ACL reconstruction (ACLR) utilizing the patellar tendon (PT) autograft include a residual defect in the PT and the potential for donor site morbidity, such as anterior knee pain and difficulty kneeling. The purpose of this study was (1) to evaluate the presence and size of PT defects following ACLR and (2) to determine if there is an association with knee pain and function. Patients who underwent ACLR with PT autograft by two surgeons between 2011 and 2023 were identified. One surgeon routinely reapproximated the PT harvest site with suture, and the other left the tendon open while closing the overlying paratenon. Included patients were at least 1 year postoperative and 13 years or older at the time of surgery. Patients underwent ultrasound evaluation of the operative knee by an independent sonographer, measuring residual PT defect width and depth. International Knee Documentation Committee, Knee Injury and Osteoarthritis Outcome Score, and Single Assessment Numeric Evaluation surveys were collected. Regression analysis determined correlations between defect size and knee outcomes. Eighty-one subjects met the criteria and completed the ultrasound and surveys. A PT defect was present in all patients at a mean follow-up of 2.97 years (1.0–9.6 years). Mean percent residual defect was 36.5 ± 17.5% of the original harvest width (mean: 10.3 mm), with a mean defect width of 3.8 ± 1.8 mm. Mean percent residual defect was significantly greater in the 57 patients who had the graft site left open (41.4 ± 13.5%) compared to the 24 patients who had the graft site reapproximated (26.1 ± 21.1%; p < 0.001). While 44.4% of patients reported moderate to extreme difficulty kneeling, it was not correlated with defect size. Patient-reported outcome scores were not correlated with defect size. A PT defect was present in 100% of patients even up to 9 years postoperatively. Defect width did not correlate with knee pain or the ability to kneel. Repeat harvesting of the PT for subsequent ACLR should be considered with caution.
Keywords: arthroscopy; ACL reconstruction; patellar tendon autograft